ANALISIS KOMUNIKASI INTRAPERSONAL MAHASISWA DALAM MEMBANGUN KEPERCAYAAN DIRI SAAT PUBLIC SPEAKING - Asti Lusiana; Lisda Yulia; Zaskia Fahrani; Sri Hertimi (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2026)
Public speaking ability is one of the crucial communication competencies for university students in facing academic and professional challenges. However, many students experience significant barriers due to low self-confidence stemming from non-constructive intrapersonal communication processes. This study aims to analyze how intrapersonal communication processes including self-talk, self-perception, and self-reflection play a role in building students' self-confidence during public speaking. The study employs a qualitative approach using the phenomenological method. Data were collected through in-depth interviews and observations of eight Communication Studies students who actively participated in public speaking activities. Data analysis utilized Braun and Clarke's thematic analysis model. The results indicate three dominant intrapersonal communication patterns: (1) positive self-talk as a pre-presentation emotion regulation strategy; (2) reframing self-perception through the internalization of previous successful experiences; and (3) post-presentation reflection as a continuous improvement mechanism. These findings indicate that the quality of intrapersonal communication directly influences students' level of self-confidence and the quality of their public speaking performance. The implications of the research affirm the importance of developing communication training programs that integrate intrapersonal communication exercises as the foundation of public speaking skills.